Mortality and long-term outcomes of palliative inotropes in ischemic and non-ischemic cardiomyopathy. (14th October 2021) - Tolia, S; Khan, M; Khan, S; Alexander, D; Soltys, M; Kamba, K; Brennan, S; Adhikari, S; Hussain, S; Joshi, A; Sciamanna, C; Narang, N; et al.
Abstract: Background: Palliative inotropes are frequently utilized for symptom management in patients with end stage heart failure who are unable to undergo durable advanced heart failure therapies. With the advent of improved medical management and early intervention, palliative inotropes may allow for improved patient outcomes than seen previously. In this study, we aim to investigate the survival and outcomes of palliative inotrope therapy and its impacts on ischemic versus non-ischemic cardiomyopathy. Methods: We retrospectively analyzed 220 patients with American Heart Association Stage D heart failure who were discharged with palliative inotrope therapy after January 1, 2010. Patients who underwent mechanical circulatory support (MCS) or those who underwent heart transplant were excluded. Those with a history of coronary artery disease, myocardial infarction, history of percutaneous intervention, or coronary artery bypass grafting were assigned to ischemic cardiomyopathy (ICM), while patients without these findings were assigned to non-ischemic cardiomyopathy (NICM). Statistical analysis was completed using Chi-Square and Student's t-tests, wherein p<0.05 was considered statistically significant. Results: Of the 220 patients, 87 had NICM as opposed to 133 with ICM. Mean age was found to be higher among patients with ICM (70 [62–79]) compared to NICM (65 [55–72], p-value <0.01). No significant difference was seen in total days on inotrope therapy (p=0.6). While more patients in both groups were placed on milrinone as opposed to dobutamine, there was no difference between patients with ischemic and NICM (p=0.66 and 0.51 respectively). Although a greater number of patients with NICM had been lost to follow up, admitted to hospice, or expired at 2 years (p<0.01), survival at 3 months, 1 year, and 2 years showed no difference between both groups. No difference was seen in number of hospitalizations or clinic visits in one year. Both groups had similar complication rates with intravenous-access related PICC line infections and new arrhythmias. (See Table). Conclusion: Despite more frequent use of durable mechanical support devices, many patients who are deemed unsuitable for invasive measures are treated with palliative inotrope therapy. We have found that there is no significant difference in survival, complications, and outcomes of patients on palliative inotropes among ischemic and NICM. These findings show the versatility of palliative inotrope therapy in end stage heart failure. Further studies with larger populations need to be evaluated. Funding Acknowledgement: Type of funding sources: None.